2016
DOI: 10.1016/j.phymed.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and ex vivo activity of an Azadirachta indica A.Juss. seed kernel extract on early sporogonic development of Plasmodium in comparison with azadirachtin A, its most abundant constituent

Abstract: The stronger activity of NA, when compared to AzaA, could not be explained by an additive or synergistic effect by other azadirachtins (B, D and I) present in NA. In fact, the addition of these compounds at 50µM concentration to AzaA did not evidence any decrease of the IC against early sporogonic stages to that obtained with AzaA alone. It is likely that other non-limonoid compounds present in NA may contribute to AzaA activity and enhanced pharmacodynamics against exflagellation both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This plant is indigenous to South Asia and abundant in the tropical belt [6]. The plant has been reported to have anti-hyperglycaemic, antibacterial [7], antifungal, anthelmintic [8], antioxidant, anti-inflammatory and antimalarial [9] activities. The plant has been reported to contain diterpenoids, triterpenoids, alkaloids, flavonoids and phenolic compounds [10].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is indigenous to South Asia and abundant in the tropical belt [6]. The plant has been reported to have anti-hyperglycaemic, antibacterial [7], antifungal, anthelmintic [8], antioxidant, anti-inflammatory and antimalarial [9] activities. The plant has been reported to contain diterpenoids, triterpenoids, alkaloids, flavonoids and phenolic compounds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The latter two, isolated from Azadirachta indica fruits, inhibit Plasmodium falciparum (W2 chloroquine-resistant strain) schizogonic replication by 50% at a concentration lower than 2 μM [11]. Azadirachtin—not active against blood stages—was found to interfere with early sporogonic development in the mosquito vector [12, 13], inhibiting 50% of ookinete formation in vitro at about 17 µM [14].…”
Section: Introductionmentioning
confidence: 99%
“…Structure-activity relationship analysis showed that the hemi-acetal moiety on carbon-11 to be critical for the observed pharmacological effect of these compounds. Azadirachtin A additionally inhibits exflagellation of gametes ex vivo and blocks development of ESS [88]. The MoA of azadirachtin A has been elucidated to be an impairment of microtubules formation during exflagellation [90].…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Azadirachta indica (Meliaceae), the neem tree native to India where it has been used for >3500 years for malaria treatment, has been comprehensively studied for its transmission-blocking activity [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A. indica fractions are active in vitro against both early- and late-stage P. falciparum gametocytes (IC 50 = 0.001 µg/mL) [ 85 , 87 ].…”
Section: Effectiveness Of Natural Products Against Transmission-blmentioning
confidence: 99%